Penegakan Hukum Tindak Pidana Penipuan Online Melalui Media Sosial di Polda Jabar Perspektif Hukum Pidana Islam: Law Enforcement of Online Fraud Criminal Acts through Social Media in the Jabar Regional Police from an Islamic Criminal Law Perspective - Muhammad Eriyan; Muhamad Kholid; Didi Sumardi (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This study examines the law enforcement of online fraud crimes conducted through social media within West Java Regional Police i based on Indonesian positive law. The increasing number of online fraud cases indicates serious challenges in law enforcement in the digital era, despite the existence of statutory regulations that clearly prohibit and impose sanctions on such acts. This research aims to analyze the law enforcement mechanisms implemented by the police and to identify the obstacles encountered in handling online fraud cases in practice. The research employs an empirical juridical method with a qualitative approach, using interviews with officers of the Cyber Crime Directorate of the West Java Regional Police, observations, and a literature review of relevant legal provisions, particularly the Indonesian Criminal Code and the Law on Electronic Information and Transactions. The findings show that, normatively, existing legal provisions have clearly regulated the prohibition and criminal sanctions for online fraud. However, in practice, law enforcement still faces several challenges, including limited digital forensic facilities, difficulties in tracing perpetrators, and coordination barriers among relevant institutions. These conditions have resulted in law enforcement efforts that are not yet optimal. Therefore, strengthening the capacity of law enforcement officers, optimizing digital law enforcement infrastructure, and enhancing inter-agency coordination are necessary to achieve effective and equitable law enforcement.